Hultgren, Anna Kristina, Frans Gregersen, & Jacob Thøgersen (eds.): En-glish in Nordic universities: Ideologies and practices. - Truong, Tran (Norsk Lingvistisk Tidsskrift, 2018)
This timely and thought-provoking volume discusses the contemporary En-glishisation of the universities of Iceland, Norway, Sweden, Denmark, and Fin-land. The Nordic countries are at the forefront of a global trend in which English is supplanting national languages in the four functions of academia: knowledge production, dissemination, education, and administration. The contributors study this trend both in terms of how Englishisation is discussed as well as how language choice is negotiated in real time by students, faculty, and staff. Book-ended by an introduction and a brief commentary are ten report chapters, two per country, which cast into stark relief the sizeable gap between ideology and practice, utilising a panoply of disciplinary approaches, to include sociology, language policy, historical linguistics, discourse analysis, ethnography, and sur-vey research. This work should prove enlightening to a wide spectrum of read-ers, be they specifically interested in language (e.g., sociolinguists, contact linguists, linguistic anthropologists) or more generally in the supra-economic consequences of globalisation on the university in late modernity.